2013
DOI: 10.1111/jvs.12072
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in plant species elevational range limits and abundances observed over nearly five decades in a western North America mountain range

Abstract: Question: Have there been shifts in abundance and distribution of alpine and sub-alpine plant species along an elevational gradient in an arid North American mountain range during the last half-century? Location: Elevational gradient in the White Mountains, California, USA (37°30′ N, 118°10′ W).Methods: We conducted a 49-yr re-survey of plant species distribution and abundance in areas originally surveyed in 1961. Species abundance data were collected along line transects between elevations of 2900 and 4000 m.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(87 citation statements)
references
References 69 publications
2
85
0
Order By: Relevance
“…Elevational range shifts at the distributional margins, however, show divergent patterns for terrestrial animals and terrestrial plants. In contrast, the few studies focusing on the trailing edge of terrestrial plants' elevational distribution (n  10) have found divergent results, with either a clear upward trend (Brusca et al 2013, Telwala et al 2013, Kopp and Cleland 2014 or no trend (Bergamini et al 2009, Frei et al 2010. For terrestrial plants, however, the trailing edge seems to be less responsive than the leading edge (Brusca et al 2013).…”
Section: Methodological Shortfallsmentioning
confidence: 96%
“…Elevational range shifts at the distributional margins, however, show divergent patterns for terrestrial animals and terrestrial plants. In contrast, the few studies focusing on the trailing edge of terrestrial plants' elevational distribution (n  10) have found divergent results, with either a clear upward trend (Brusca et al 2013, Telwala et al 2013, Kopp and Cleland 2014 or no trend (Bergamini et al 2009, Frei et al 2010. For terrestrial plants, however, the trailing edge seems to be less responsive than the leading edge (Brusca et al 2013).…”
Section: Methodological Shortfallsmentioning
confidence: 96%
“…Winter snow accounts for much of the yearly precipitation, which varies with elevation, forming a gradient where precipitation is positively correlated with elevation and temperature is negatively correlated with elevation (Hall, ). Between 1961 and 2010, mean growing season temperatures increased by 1.0°C in this mountain range (Kopp & Cleland, ).…”
Section: Methodsmentioning
confidence: 99%
“…Supporting information Appendix S1: Figure shows photographs of typical individual plots. At the 2,900 and 3,100 m elevations, sagebrush plants are widely spaced, with one sagebrush plant every 1.9 and 1.7 m, respectively (data from 2010 transect surveys reported in Kopp & Cleland, ). At 3,750 m, sagebrush plants in patches were more closely spaced (Supporting information Appendix S1: Figures and ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, intraspecific competition can drive niche partitioning, making overall resource use more efficient (Boyden et al, 2008) and can increase tolerance to herbivory (McNutt et al, 2012). Further research into biotic interactions in E. regnans forests is needed to assess the likelihood of elevational range shifts in this ecosystem as the climate continues to change (le Roux et al, 2013;Kopp & Cleland, 2014). Further research into biotic interactions in E. regnans forests is needed to assess the likelihood of elevational range shifts in this ecosystem as the climate continues to change (le Roux et al, 2013;Kopp & Cleland, 2014).…”
Section: Effects On Densitymentioning
confidence: 99%